The compatible action graphs for finite cyclic 2-groups - Sahimel Azwal, Sulaiman; M. S., Mohamed; Yuhani, Yusof; M. K., Shahoodh; H. A., Hamid (Penerbit UMP, 2020)
A graph namely the compatible action graph is introduced by extending the results on the compatible pairs of actions for cyclic 2-groups. Some properties of compatible action graphs are presented. In addition, the special types of compatible action graphs are given.